(untitled) (International Journal of Geoscience, Engineering and Technology, 2024)
With the growth of the population, there is the occupation of areas that are not suitable for construction and even the occupation with undesigned buildings. Consequently, risk areas and accidents with landslides have been increasingly frequent in Brazil. Cities with high elevation relief, such as Teófilo Otoni, face this problem even more. The objective of this study was to highlight some risk areas in the Manoel Pimenta neighborhood in the city of Teófilo Otoni. For this survey, the methodology of classification of risk areas of the Ministry of Cities was used. Risk grade areas R3 and R4 were found, showing the need to implement measures in order to reduce or prevent the impacts caused in these areas.